HOW EXCHANGE RATE AND STOCK MARKET VOLATILITIES AFFECT FOREIGN DIRECT INVESTMENT IN NIGERIA: A NON-LINEAR APPROACH - ABDULLAHI, KABIR (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2024)
This paper examines how the exchange rate and stock market volatilities affect foreign direct investment (FDI) in Nigeria, using monthly time-series data from 2000 to 2022. The paper applies a Non-linear Autoregressive Distributive Lag (NARDL) method to capture the asymmetric effects of positive and negative shocks from the real exchange rate volatility (XVOL), the stock market volatility (SMVOL), and the real growth domestic product (RGDP) on FDI. The paper finds that there is a long-run cointegration relationship among the variables and that both positive and negative shocks from XVOL and SMVOL have significant negative effects on FDI in the short and long run. In contrast, positive shocks from RGDP have a significant positive effect on FDI in the long run, but an insignificant positive effect in the short run. These results imply that the Nigerian government should stabilise the exchange rate and the stock market to enhance FDI inflows and economic growth